Sn-119 magic angle spinning NMR of nanocrystalline SnO2 - Sabarinathan, V.; Chandran, C. Vinod; Ramasamy, S.; Ganapathy, Subramanian (Journal of Nanoscience and Nanotechnology, 2008)
Nanocrystalline SnO2 samples of different grain sizes, prepared by inert gas condensation technique (IGCT) and chemical precipitation method and conforming to the tetragonal phase, have been studied by variable speed (3-10 kHz) Sn-119 MAS NMR at 11.74 Tesla field. Sn-119 solid-state NMR results show that the IGCT prepared samples have good crystallinity and phase purity compared to the samples prepared by the chemical method. The determination of Sn-119 chemical shielding parameters (delta(iso), Delta delta and eta) from slow MAS spectra shows that the Sn-119 isotropic chemical shift (delta(iso)) is strongly influenced at smaller grain sizes, attributable to the change in the O2- local symmetry for the surface Sn-119 ions at smaller grain sizes. The observed line widths in MAS spectra are significantly larger than the life-time broadening due to spin-lattice (T-1) and spin-spin (T,) relaxation. The Sn-119 MAS NMR spectra are thus inhomogeneously broadened by a distribution of isotropic chemical shifts, the line broadening increasing with decrease in grain size.
Keywords: Hydrolysis; IGCT; MAS NMR; nanocrystalline SnO2

Perturbations to Al-27 electric field gradients in nanocrystalline alpha-Al2O3 studied by high-resolution solid-state NMR - Sabarinathan, V.; Ramasamy, S.; Ganapathy, Subramanian (Journal of Physical Chemistry B, 2010)
Al-27 solid-state NMR has been employed to study the perturbations to Al-27 electric field gradients for the aluminum environments in nanocrystalline alpha-alumina. Triple quantum magic angle spinning experiments show that the octahedral aluminum coordination remains unchanged down to 12 nm, although severe perturbations to Al-27 electric field gradients are noticed at 28 nm and below. 3Q-MAS and SATRAS experimental data of nano alpha-alumina have been analyzed through extensive spectral simulations to probe Al-27 electric field gradients of aluminum in the grains and grain boundaries. While the aluminum in the grains has a unique field gradient tensor, the same octahedrally coordinated aluminum environments in the grain boundaries suffer a distribution of electric field gradients. This is evidenced by data analysis of both 3Q-MAS and SATRAS spectra. By invoking the Gaussian isotropic model, in which the (C-Q, eta(Q)) parameter space is discretely sampled by the Czjzek distribution, we have been able to analyze the Al-27 SATRAS spectra of nanocrystalline alpha-alumina samples having grain sizes of 52, 28, 20, and 12 nm. Good agreement between experimental and simulated spectra has led to the quantitative determination of grain and grain boundary components in these materials.

Evaluating a new high-throughput twin-arginine translocase assay in bacteria for therapeutic applications - Ghosh, D. (Current Microbiology, 2017)
The twin-arginine translocase (Tat) pathway is involved in the transport of folded proteins in bacteria, and has been implicated in virulence and pathogenesis. A simple but efficient assay based on the quantification of the exopolysaccharide colanic acid was developed as a new means to study Tat function. Colanic acid contains a methylpentose (l-fucose) component, and its production is directly linked to the Tat pathway through the transport of enzymes involved in polysaccharide biosynthesis. Monitoring of l-fucose levels can be applied for identification of new Tat substrates and high-throughput screening of Tat inhibitors for therapeutic applications.

Molecular features of bile salt hydrolases and relevance in human health - Chand, D.; Avinash, V. S.; Yadav, Y.; Pundle, A. V.; Suresh, C. G.; Ramasamy, S. (Biochimica et Biophysica Acta - General Subjects, 2017)
Background: Bile salt hydrolase (BSH) enzyme is responsible for the de-conjugation of bile salts by commensal bacteria, thus playing a vital role in their colonization and survival in the mammalian intestine and determination of their probiotic potential. Further, bile deconjugation also leads to lowering of cholesterol and alterations in energy homeostasis, thus making BSH a clinically important enzyme. Scope of the review: Many recent observations have indicated that BSH may be involved in a multifaceted array of roles, directly or indirectly in the host and microbial physiology. BSH paralogues have now been found to occur in different microbes including free-living and pathogenic bacteria and Archaea. BSHs from various sources also show differential activity and substrate spectrum. Certain bacteria are known to possess multiple genes for BSH enzymes. BSHs have been reported to influence different metabolic phenomena, including bacterial pathogenesis and the maintenance of lipid and glucose homeostasis in the host. These observations necessitate an intense study into the biochemical, structural and regulatory features of BSH enzymes to better understand their role in regulating bacterial and host metabolism. Major conclusions: In this review, the available information on the characteristics of BSH enzymes have been organized in order to understand their interactions with a wide range of substrates and their myriad physiological roles, from bile resistance to signalling mechanisms. General significance: A detailed exploration of BSH architecture and regulation could provide insights into its evolution and a deeper appreciation of the multiple functions of this enzyme relevant to healthcare.

Structural insights into the unique inhibitory mechanism of Kunitz type trypsin inhibitor from Cicer arietinum L. - Bendre, A.D.; Suresh, C.G.; Shanmugam, D.; Ramasamy, S. (Journal of Biomolecular Structure and Dynamics, 2018)
Kunitz-type trypsin inhibitors bind to the active pocket of trypsin causing its inhibition. Plant Kunitz-type inhibitors are thought to be important in defense, especially against insect pests. From sequence analysis of various Kunitz-type inhibitors from plants, we identified CaTI2 from chickpea as a unique variant lacking the functionally important arginine residue corresponding to the soybean trypsin inhibitor (STI) and having a distinct and unique inhibitory loop organization. To further explore the implications of these sequence variations, we obtained the crystal structure of recombinant CaTI2 at 2.8Å resolution. It is evident from the structure that the variations in the inhibitory loop facilitates non-substrate like binding of CaTI2 to trypsin, while the canonical inhibitor STI binds to trypsin in substrate like manner. Our results establish the unique mechanism of trypsin inhibition by CaTI2, which warrant further research into its substrate spectrum. Abbreviations BApNA Nα-Benzoyl-L-arginine 4-nitroanilide BPT bovine pancreatic trypsin CaTI2 Cicer arietinum L trypsin inhibitor 2 DrTI Delonix regia Trypsin inhibitor EcTI Enterolobium contortisiliquum trypsin inhibitor ETI Erythrina caffra trypsin inhibitor KTI Kunitz type inhibitor STI soybean trypsin inhibitor TKI Tamarindus indica Kunitz inhibitor Communicated By Ramaswamy H. Sarma.

Structure and function of a highly active Bile Salt Hydrolase (BSH) from Enterococcus faecalis and post-translational processing of BSH enzymes - Chand, D. (Biochim Biophys Acta., 2018)
Bile Salt Hydrolase (BSH), a member of Cholylglycine hydrolase family, catalyzes the de-conjugation of bile acids and is evolutionarily related to penicillin V acylase (PVA) that hydrolyses a different substrate such as penicillin V. We report the three-dimensional structure of a BSH enzyme from the Gram-positive bacteria Enterococcus faecalis (EfBSH) which has manifold higher hydrolase activity compared to other known BSHs and displays unique allosteric catalytic property. The structural analysis revealed reduced secondary structure content compared to other known BSH structures, particularly devoid of an anti-parallel β-sheet in the assembly loop and part of a β-strand is converted to increase the length of a substrate binding loop 2. The analysis of the substrate binding pocket showed reduced volume owing to altered loop conformations and increased hydrophobicity contributed by a higher ratio of hydrophobic to hydrophilic groups present. The aromatic residues F18, Y20 and F65 participate in substrate binding. Thus, their mutation affects enzyme activity. Docking and Molecular Dynamics simulation studies showed effective polar complementarity present for the three hydroxyl (-OH) groups of GCA substrate in the binding site contributing to higher substrate specificity and efficient catalysis. These are unique features characteristics of this BSH enzyme and thought to contribute to its higher activity and specificity towards bile salts as well as allosteric effects. Further, mechanism of autocatalytic processing of Cholylglycine Hydrolases by the excision of an N-terminal Pre-peptide was examined by inserting different N-terminal pre-peptides in EfBSH sequence. The results suggest that two serine residues next to nucleophile cysteine are essential for autocalytic processing to remove precursor peptide. Since pre-peptide is absent in EfBSH the mutation of these serines is tolerated. This suggests that an evolution-mediated subordination of the pre-peptide excision site resulted in loss of pre-peptide in EfBSH and other related Cholylglycine hydrolases.
Keywords: autocatalytic processing; Bile salt hydrolase; molecular dynamics; Mutagenesis; Polar complementarity; X-ray crystallography